Perceptions about Epilepsy in the Limpopo Province of the Republic of South Africa - ML Mangena-Netshikweta (AOSIS, 2003)
In rural African communities, there are widespread beliefs that epilepsy is due to possession of bewitchment by evil spirits or the devil. There is also a belief that the transmission of the disease is by physical contact, such as by saliva (Osuntokun 1990:106). In central Africa, as well as in Sub-Saharan Africa, epilepsy is attributed to the presence of a lizard in the brain, and epileptic fits occur whenever the lizard moves ( Haddock 1993:118 ; Nyame 1997:143 ). Such perceptions toward epilepsy and a person with epilepsy, in indigenous Africa, are invariably unfavourable and unfounded as they reflect mythical beliefs about the disease.